REAKSI BERDUKA PADA PENYINTAS KEHILANGAN BUNUH DIRI: LAPORAN KASUS - Dyani Pitra Velyani; Mulia Rahmansyah; Ika Nur Fitriana (Jurnal Akta Trimedika, 2024)
World Health Organization reported that there were more than 700,000 deaths due to suicide each year. Suicide incidents were like stones thrown into calm lakes, causing widespread ripples. Levi-Belz, in his study, stated that each suicide case affected an average of five family members and up to 135 individuals, including partners, colleagues, and the community. Suicide loss survivors were at a higher risk of experiencing complicated grief, depression, and suicide compared to the bereaved due to causes. Stigmatisation of suicide behavior and suicide loss survivors made them reluctant to disclose themselves, leading to less access to the help they needed. This case report described a 51-year-old woman experiencing grief reactions due to her daughter's suicide. She exhibited denial, anger, guilt, and self-blame. Her decision not to disclose her condition to family and relatives forced her to face emotional and mental turmoils on her own. This patient is still in the acute phase of grief reactions and is receiving psychological intervention in an individual setting. The assessment of suicide risk and ongoing observation of persistent psychological symptoms should be conducted periodically.